Design And Implementation Of Scientific Publication Cms With Peer Review Tools For Academic Institutions - Jumagul Nurakun Kyzy; Mehmet Tekerek (MANAS: Journal of Engineering)
This paper describes efforts underway to construct a Scientific Publication Content Management System (SPCMS) with Peer Review Tools (PRT) for Academic Institutions. Firstly, known Scientific Publication processes have been reviewed and online publication process was chosen as a model for developing a scientific content publication and management system. Next, the developed system will be implemented as a case study to Kyrgyzstan-Turkey Manas University scientific journal publication system. Since it is aimed to construct an online only journals, the system is supposed to be fast-tracking, fully manageable and, on the other hand, it should be highly secure since all the manuscripts are to be stored on the system. To undertake such problems as fast tracking, speedy data processing and security was decided to implement self-developed system by using PHP and AJAX programming on Apache server with MySQL data base application.The result of this research is an automated publishing system for scholar manuscript publications, from submission through peer review, aggregate, manage and publish university journals, utilizing a single, dynamic destination.